SEROLOGICAL DIAGNOSIS OF MODERN CHOLERA USING LIPOSOMAL ENTEROTOXIC DIAGNOSTICUM IN COMPLEMENT FIXATION TEST - I. V. Savelyeva (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. The possibility of serological diagnosis of cholera using cholera enterotoxic diagnostics kit in complement fixation test to detect anti-enterotoxic antibodies in sera of patients with cholera caused by hybrid variants of the El Tor biovar has been demonstrated. In patients with mild course of cholera anti-enterotoxic antibodies were detected in titres 1:50 and 1:200 in paired sera obtained on the 7th and 14th days of disease, respectively (fourfold titre increase). In patients with the course of medium severity 32-fold titre increase was recorded from the titre 1:100 in serum obtained on the fifth day of disease till the titre 1:3200 — on the twelfth day of disease. Antibodies titers reached 1:1600 and 1:800 were revealed in two medium course patients (adult and infant of 10 months) on the sixth day of disease.